1992
DOI: 10.1111/j.1532-5415.1992.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline in Cerebrovascular Dementia

Abstract: Treatment with pentoxifylline may slow the progression of dementia in patients who meet DSM-III criteria for "multi-infarct dementia" and who also have clinical and neuroradiological evidence of cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
4

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 35 publications
(48 reference statements)
2
26
0
4
Order By: Relevance
“…Several studies have investigated the use of pentoxifylline, which has been approved for use in peripheral vascular disease (intermittent claudication) and is reported to have a 'hemorheological' mode of action, i.e. it is thought to affect the microcirculation, increasing capillary blood flow and thereby improving tissue oxygenation [22,23]. These studies suggested that the treatment may be beneficial but the differences between patients receiving treatment and those given the placebo were small and often not statistically significant.…”
Section: Curative Treatmentmentioning
confidence: 99%
“…Several studies have investigated the use of pentoxifylline, which has been approved for use in peripheral vascular disease (intermittent claudication) and is reported to have a 'hemorheological' mode of action, i.e. it is thought to affect the microcirculation, increasing capillary blood flow and thereby improving tissue oxygenation [22,23]. These studies suggested that the treatment may be beneficial but the differences between patients receiving treatment and those given the placebo were small and often not statistically significant.…”
Section: Curative Treatmentmentioning
confidence: 99%
“…• Métodos de neuroimagem (TC, RM -volume lesional, número e topografia das lesões, gravidade de leucoaraiose, grau de atrofia e dilatação ventricular) 7,9,20,76 • Eletrofisiológicos (EEG espectral, coerência eletrencefalográfica, eletro-oculografia, análise do ciclo sonovigília, potenciais cognitivos, potenciais motores) 1,19,23,35,44,45,48,67,72,76 • Bioquímicos e hormonais (interleucina-1, histamina, fator de necrose tissular, complexos imunes circulantes, alfa-1-antitripsina e alfa-2-macroglobulina, GH, PRL, androsterona, cortisol urinário; CRH, neuropeptídeos, endotelina-1 e colinesterase no LCR) 5,[11][12][13][14]37,47,57,58,71,82 • Neuropsicológicos (vários conjuntos de testes, baterias de testes, escalas de gravidade de demê-ncia) 6,8,26,35,53,59,60,67,68,79 • Provas funcionais (SPECT, PET, espectroscopia por RM) 10,20,21,49,50,81…”
Section: Tabela 1 Métodos Complementares Utilizados Em Estudos Recenunclassified
“…Um número muito pequeno de pacientes é habitualmente estudado, com divisões em subgrupos que tornam ainda mais difícil a interpretação dos resultados (p.ex. pentoxifilina 6 , citidina 29 , CDP-colina 13 , bifemelane 72 ). Como mencionado, uma miríade de métodos de avaliação de eficácia é utilizada, tornando difícil a comparação de diversas intervenções.…”
Section: Tratamento Medicamentoso Da Dvaunclassified
“…169 It has been widely used in the treatment of intermittent claudication and it has also been claimed to slow the progression of vascular dementia. 170 Pentoxifylline has also been marketed and used as a treatment for acute stroke in several countries, although its efficacy and safety in this situation have never been established. 169,171 Many other treaments with potential but inadequately evaluated neuroprotective actions are widely used in some countries.…”
Section: Other Potential Neuroprotective Drugsmentioning
confidence: 99%